Effects of Fluoride Release on Enamel Color Alteration - Mahmoud Nabil El-Saafin; Firas Hadad; Victor Suciu; Marioara Moldovan; Mariana Pacurar (European Scientific Journal, ESJ, 2017)
The aim of this study is to evaluate teeth discoloration after the usage of adhesive fluoride release. Material and Method: 80 extracted healthy premolars divided into two groups were used in the study, with metal brackets being bonded in both groups,. The first group universal adhesive was applied (transbond light cure adhesive paste-Transbond XT), whereas in the second group fluoride releasing bonding material was used (opal bond MV composite and opal seal). The measurement of color parameters was performed using the spectrophotometer vita easyshade 4.0 to calculate ΔL, Δa, Δb, and ΔE. Statistical Analysis: 3-way mixed analysis of variances (ANOVA) was used to compare ΔE before using adhesive material and after the procedure. On the other hand, it was used to compare Δa, Δb, and ΔL before and after using adhesive material. The statistical significance level was established at P< 0.05. Boferroni correction was used to create mean differences between the results. Results: The result of this study showed that ΔE* values were increased in all groups. The mean difference of ΔE* value in the first group (3M adhesive material) was 2.54± 1.57. At the same time, the ΔE value in opal adhesive group was 4.43±5.4. These results showed that fluoride seal had direct effect on enamel color after a period of three months teeth storage. Results showed above the normal limit and produced visible color change on the surface of the teeth after finishing procedure. On the other hand, ΔL values were increased in both groups, with a significant difference in the first group (p value 0.04) and with no significant difference in the second group (p value 0.239). Conclusion: The highest color changes were observed after the finishing procedure in opal bond MV composites and the opal seal groups. This was done by increasing ΔE value due to the presence of fluoride release adhesive structure. Transbond light cure adhesive past-Transbond XT had acceptable clinical change after the debonding and finishing procedure by increasing ΔE value.